FORESIGHT - ECOSUSTAINABLE DETERMINANTS OF STRATEGIC MODERNIZATION OF HYDROELECTRIC POWER PLANTS - L. Dovgan; M. Shkrobot (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the paper the foresight methodology as an ecosustainable determinants of strategic modernization of hydroelectric power plants in the conditions of the external challenges and threats is revealed. The strategic concepts of modernization and a mechanism of strategic modernization of hydroelectric power plants on the principles of public-private partnerships is allocated. Recommendations on the implementation of the results of the strategic foresight to the modernization of hydroelectric power plants in the interaction of public and private agents are formulated.